Corruption in Spain and Catalonia after 2008 - Myśliwiec, Małgorzata; Stachowicz, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The authors decided to deal with the theme of the influence of corruption on the political processes in contemporary Spain and Catalonia. The investigation of this problem requires the reference to both: a political situation in entire state and in the peripheral region, included in the territorial range of Spain.
Keywords: Catalonia; Spain; corruption; economic crisis of 2008